2009
DOI: 10.17221/16/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of some botanical insecticides against Spodoptera littoralis Boisduvala (Lepidoptera: Noctudiae), Myzus persicae Sulzer (Hemiptera: Aphididae) and Tetranychus urticae Koch (Acari: Tetranychidae)

Abstract: Pavela R. (2009): Effectiveness of some botanical insecticides against Spodoptera littoralis Boisduvala (Lepidoptera: Noctudiae), Myzus persicae Sulzer (Hemiptera: Aphididae) and Tetranychus urticae Koch (Acari: Tetranychidae). Plant Protect. Sci., 45: 00-00.Abstract: Biological efficiency of botanical insecticides was determined that were obtained from Pongamia glabra, azadirachta indica and Chrysanthemum cinerariifolium against Spodoptera littoralis, Myzus persicae and Tetranychus urticae on greenhouse plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 14 publications
0
36
0
3
Order By: Relevance
“…According to Pavela (2009) Neem products may exhibit systemic effect and could affect on larval bruchids. Maheshkumar et al (2000) studied the systemic effect of eight neem formulations including neemAzal-T/S on the green leafhopper (Nephotettis virescens Distant.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pavela (2009) Neem products may exhibit systemic effect and could affect on larval bruchids. Maheshkumar et al (2000) studied the systemic effect of eight neem formulations including neemAzal-T/S on the green leafhopper (Nephotettis virescens Distant.)…”
Section: Discussionmentioning
confidence: 99%
“…Pavela (2009) reported that biological products containing azadirachtin are unstable under illumination, have rapid photodegradation under UV radiation, and are susceptible to low temperatures and rainfall. NeemAzal was less effective in 2013 due to heavy rains in June coinciding with the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In general, botanical insecticides are less toxic than the synthetic ones and they degrade faster (ABBASSY; ABDELGALEIL; RABIE, 2009). Another advantage of botanical insecticides is the chemo-biodiversity of plants, which provides a variety of bioactive compounds against pests and significantly reduces the selection of resistant ones (PAVELA, 2009;PINO;SÁNCHEZ;ROJAS, 2013). The insecticidal activity of COR can be attributed to several identified chemical constituents, which belong to monoterpene, sesquiterpene, and diterpene classes (GERIS et al, 2008;LEANDRO et al, 2012).…”
Section: O R + T R I a Z O P H O S C O R + C H L O R P Y R I F O S mentioning
confidence: 99%
“…Sentetik ilaçların insan, hayvan ve bitki sağlığı üzerinde yarattığı olumsuz etkilerini kaldırmak için; zararlılarla mücadelede yeni, etkili ve alternatif maddeler bulma ihtiyacı ortaya çıkmıştır. Bu nedenle bir çok bitki ekstraktının M. persicae'nin mücadelesinde önemli insektisit etkiye sahip olduğu yapılan çalışmalarla ortaya konulmuştur (Pavela, 2009;Pavela ve ark., 2009;González ve ark., 2011;Salaria ve ark., 2012;Ghosh, 2015;Nia ve ark., 2015). Bu çalışmada da bazı bitki ekstraktlarının söz konusu zararlının biyolojisine etkisi ortaya konularak, entegre savaşım yönetiminde zararlılarla mücadelede kullanılma potansiyelleri belirlenmiştir.…”
Section: Introductionunclassified